Test Of Secondary Metabolites And Total Phenols Of Robusta Coffee Grass (Coffea Canephora) Bener Meriah District - Muttakin muttakin; Sri Setiawaty; Riska Imanda; Widya (LPPM Universitas Malikussaleh, 2024)
Coffee is one of the plantation commodities which has an important role in Indonesia's economic activities. The development of coffee processing, both on a small scale and on an industrial scale, will produce by-products called coffee waste. Coffee grounds waste is waste produced from the coffee processing process which reaches almost 45% of total production. The aim of this research was to determine the secondary metabolite and total phenol content of robusta coffee grounds in Bener Meriah Regency. The method used in this research is the experimental method. The resulting coffee grounds will be extracted using a solvent, and the resulting extract will be tested for secondary metabolites and total phenols. This test will be carried out in the chemistry laboratories of FKIP Unimal and FKIP USK. The results of testing the secondary metabolite content and total phenol content in Robusta coffee grounds were Alkaloids (Dragendrof, Mayer and Wagner), Saponins, Flavonoids, Polyphenols and Steroids, and the total phenol content was 87.38 (mg GAE/g extract).